the recipe: much more than a process in the kitchen - Gonzales de la Flor, Celia Rosa (2013)
This essay is a different view of an underlying studies on cooking and food theme, and the social science community does not feel the need to consider , evaluate and analyze this issue , much less a culinary recipes , from a thoughtful and scientific gaze , which contributes to the knowledge of the culinary roots, its historical development partner , the process of production of identities of some groups in the country, even to transit routes dynamism of modernity of the new century . No doubt today ‘s recipe is one of the main gastronomic products expected by farmers, chefs , scholars, housewives or public, is given by this corollary obvious and therefore , the author takes a direct reflection from the social sciences, and invites with healthy challenge for social scientists take care of what they can learn , study, interpret and explain , in the current context of the so called ‘ Peruvian gastronomic boom’.